Visual tourism and post-colonialism: imaginative geographies of Africa in a Portuguese travel magazine - Brito-Henriques, Eduardo (2014)
This paper is about tourism, visual culture, and imperialism in the post-colonial present. International literature on these issues has been especially focused on the experience of British and French post-colonialism. Few studies have addressed this issue regarding other post-colonial realities. This paper runs counter to that fact by analysing the visual touristic discourse produced in the post-colonial Portugal. The paper examines the way the sub-Saharan Africa is represented in a Portuguese travel photo-magazine – the Blue Travel magazine – so as to verify the extent to which the ideology of colonialism continues to shape the post-colonial touristic discourse in this former colonizing country of the southern Europe. More than 522 photographs were analysed. Using visual methodologies, the paper concludes that many aspects of the photographs contain encoded encomiastic messages of colonialism and participate in a discursive construction of Africa that was clearly shaped by an imperialist gaze. The paper suggests that not only there is an obvious nostalgia for empire in the Portuguese touristic discourse on sub-Saharan Africa, but also that many imperialist myths continue to circulate diffusely within the Portuguese post-colonial society and to shape the way sub-Saharan Africa is touristically imagined.